Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Remaja Putri Di SMPN 17 Tangerang Tahun 2022 - Sandra Dewi, Elvira; Mardhiati, Retno; Musniati, Nia (Fakultas Kedokteran Universitas Trisakti, 2023)
Background The problem of anemia still exists today, although there have been many treatments for adolescent anemia. This study aimed to determine the factors associated with the incidence of anemia in adolescent girls at SMPN 17 Tangerang in 2022. Methods This study uses a cross-sectional design. The sample is 150 students with Quota Sampling. Collecting data using a questionnaire and direct measurements on hemoglobin levels, weight, and height. The instruments used were filling forms for hemoglobin levels, weight, and height and questionnaires for the variables of knowledge, mother's education, parents' income, menstrual patterns, eating patterns, and consumption of blood-added tablets (TTD). The analysis in this study is univariate and bivariate (Chi-square). Results The results of the univariate analysis showed anemia (40%), poor knowledge (56.0%), high maternal education (74.7%), high parental income (59.3%), abnormal menstrual pattern (61.3% ), poor diet (73.3%), normal nutritional status (70.7%), consumption of Blood Supplementary Tablets (TTD) was not good (97.3%). The results of the bivariate analysis obtained four variables related to the incidence of anemia in adolescent girls at SMPN 17 Tangerang, namely the variables of knowledge (p=0,048), mother's education (p=0.042), parents' income (p=0.038), dietary habit (p=0.038). However, there were unrelated ones, namely menstrual patterns, nutritional status, and consumption of blood-added tablets. Conclusions Variables related to the incidence of anemia were knowledge, the mother's education, the parent's income, and eating patterns (dietary habits).